Effect of Iodinated Contrast Medium in Diabetic Rat Kidneys as Evaluated by Blood-Oxygenation-Level–Dependent Magnetic Resonance Imaging and Urinary Neutrophil Gelatinase-Associated Lipocalin. Issue 6 (December 2015) - Li, Lu-Ping; Lu, Jing; Franklin, Tammy; Zhou, Ying; Solomon, Richard; Prasad, Pottumarthi V.
<x xml:space="preserve">Abstract</x> Objectives The objective of this study was to assess whether streptozotocin (STZ)-induced diabetic rats develop iodinated contrast-induced acute kidney injury. The intrarenal R2* (=1/T2*) was evaluated continuously before, during, and after contrast administration. Renal injury was confirmed using urinary neutrophil gelatinase-associated lipocalin measurements. Materials and Methods Six Sprague-Dawley rats were administered with STZ to induce diabetes (group 1). R2* was measured before, during, and after administration of iodixanol. R2* readings were sampled from 4 renal regions: inner medulla, inner stripe of outer medulla (ISOM), outer stripe of outer medulla, and cortex. Peak R2* and initial upslope of R2* increase after iodinated contrast were calculated. Data from 12 nondiabetic rats pretreated with nitric oxide synthase and prostaglandin inhibitors to induce susceptibility to contrast-induced acute kidney injury (pretreatment model) from a previous study were reanalyzed for peak R2* and initial upslope of R2* increase after contrast. Six of these animals received saline (group 2), and the other 6 received furosemide (group 3) before iodixanol. Results Peak R2* and initial upslope of R2* increase were used as blood-oxygenation-level–dependent response parameters. R2* in ISOM was comparable in all 3 groups before administration of furosemide/saline. Except for the furosemide group, ISOM showed a rapid increase in R2* immediately after contrast administration. Unlike the L-NAME- and indomethacin-treated groups, the diabetic group showed a quick reversal of R2* toward baseline measurements after contrast administration. Urinary neutrophil gelatinase-associated lipocalin indicated significant increase in diabetic rats 4 hours after contrast administration. The observed trends with peak R2* and initial upslope of R2* increase in renal ISOM were in agreement with those of urinary neutrophil gelatinase-associated lipocalin. Conclusions The STZ-induced diabetic rat may be suitable for studying the effects of iodinated contrast on renal oxygenation status and may mimic human condition closer than the pretreatment model described before. The peak R2* value and initial upslope of R2* in ISOM appear to be effective magnetic resonance imaging markers to predict renal injury after administration of an iodinated contrast agent.